Generators of dynamical chaos based on FPGA - Kozhagulov, Ye.T.; Ibraimov, M.K.; Khokhlov, S.A.; Sagidolda, Ye.; Zheksebay, D.M. (Recent Contributions to Physics, 2014)
Chaotization of motions in deterministic nonlinear systems are of great interest, as evidenced by the rising tide of scientific information. This is due tovariety of application solutions using various generators of chaotic signals, such as the expansion of the spectral band signal, reception and transmission of confidential information signal, etc. To implement these objectives, we chose Programmable Logic Array (FPGA), which improves the performance of generators due to parallel data procession. This paper shows the results of using the new method implementation of chaotic generators based on differential equations and dynamical systems mapping. Digital circuitry is made by means of integral schemes of Field Programmable Gate Array. Also shown the possibility of using the proposed complex digital electronic technology to obtain ultra-wideband, microwave, chaotic signals with different statistical properties.